Challenges of Super-Super Obese Patient Presenting for Neurosurgery: A Case-Based Review - Sapna Suresh; Ajay P. Hrishi; Ashitha Arumadi; Ranganatha Praveen (Journal of Neuroanaesthesiology and Critical Care)
With the rising prevalence of extreme obesity, their perioperative neurosurgical management demands special attention. We report the case of an acromegalic male with a body mass index as high as 64.12 kg/m2 who presented for craniotomy and resection of a pituitary tumor under general anesthesia. Through this report, we introduce the readers to this newer concept of the highest grade of obesity in the context of neurosurgery, explain the perioperative concerns, and reiterate the need for careful drug dosing, ventilation targets, positioning requirements, thorough cardiac and airway evaluation, and preparedness for adverse events. This report also highlights the fact that a well-planned and managed case can still turn out uneventful in the presence of multiple comorbidities like diabetes mellitus, adrenocortical insufficiency, hypothyroidism, and acromegaly. Advances in airway management, regional anesthesia, and perioperative point-of-care ultrasound have made it possible to formulate a safe anesthetic plan tailored to the patient's needs.